2022
DOI: 10.3390/ijms23073860
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vitamin D in Prophylaxis and Treatment in Tuberculosis Patients

Abstract: Vitamin D plays a crucial role in many infectious diseases, such as tuberculosis (TB), that remains one of the world’s top infectious killers with 1.5 million deaths from TB in 2021. Vitamin D suppresses the replication of Mycobacterium tuberculosis in vitro and showed a promising role in TB management as a result of its connection with oxidative balance. Our review encourages the possible in vivo benefit of a joint administration with other vitamins, such as vitamin A, which share a known antimycobacterial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
(68 reference statements)
0
11
0
1
Order By: Relevance
“…Previous studies suggested that multivitamin supplementation is beneficial to the prognosis of TB patients, and its effect may be through inhibiting growth, even killing Mycobacterium TB, and improving the internal environment of oxidative stress. 30 , 31 Therefore, BMI may not provide a comprehensive assessment of nutritional levels in TB patients. The parameters of GNRI include height, weight, and albumin, and are also improved by NRI recommended by PNNs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that multivitamin supplementation is beneficial to the prognosis of TB patients, and its effect may be through inhibiting growth, even killing Mycobacterium TB, and improving the internal environment of oxidative stress. 30 , 31 Therefore, BMI may not provide a comprehensive assessment of nutritional levels in TB patients. The parameters of GNRI include height, weight, and albumin, and are also improved by NRI recommended by PNNs.…”
Section: Discussionmentioning
confidence: 99%
“…The low toxicity of vitamin K in humans may ease such attempts. The possible in vivo benefit of a joint administration with vitamin D shown to be protective in other infectious diseases is encouraged to be investigated [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that prevention and treatment of different conditions require different concentrations of vitamin D. Cutoff values in vitamin D concentration supported by high-level evidence studies are still not available. However, it appears that for interventions in bone mineral density, dental health, fracture risk, or tumorigenesis, benefits are obtained starting at 25OHD concentrations of 30 ng/mL [ 114 ]. For tuberculosis prevention, in vitro studies have indicated a cholecalciferol concentration of 4 µg/mL as adequate to slow proliferation in culture.…”
Section: Current Clinical Trials Using Vitamin D In Autoimmune Diseasesmentioning
confidence: 99%
“…This is a much higher concentration, but potentially achievable due to local hydroxylation performed by macrophages. At the same time, in vivo studies did not provide a clear conclusion [ 114 , 115 ]. A number of research and review papers, including those cited in this paper, point to the need for robust randomized controlled trials on large groups of patients to determine a dose of vitamin D supplementation that would demonstrate long-term benefits with a safety profile in ADs.…”
Section: Current Clinical Trials Using Vitamin D In Autoimmune Diseasesmentioning
confidence: 99%